Experience of a program for the reduction of cardiovascular risk factors in secondary school teachers.: Experiencia de un programa para reducción de factores de riesgo cardiovascular en docentes de educación secundaria. - Montalvo, Raul (2024)
Introduction: Physical inactivity among secondary school teachers increases cardiovascular and metabolic risks, highlighting the need for effective intervention strategies. Objective: To compare changes in body composition, lipid profile, and blood pressure following a physical exercise and nutritional education program. Methods: A prospective observational study was conducted with 556 teachers, divided into a program group (274) and a no-program group (282). The program included guided weekly exercises and nutritional workshops over three months. Baseline and final measurements assessed weight, body mass index (BMI), blood pressure, lipid profile, and body composition using tetrapolar bioimpedance. Statistical analyses used Student's t-test to compare deltas between groups, with p<0.05 considered significant. Results: The program group showed reductions in systolic blood pressure (SBP) (-7.0±10.6 mmHg; p<0.001), body fat (-3.0±15.4%; p<0.001), and total cholesterol (-12.2±45.6 mg/dL; p=0.002). HDL cholesterol increased (+8.8±40.8 mg/dL; p=0.007). No significant changes were observed in these indicators in the no-program group. Weight and BMI did not vary significantly in either group. Conclusion: The program improved cardiovascular risk factors and body composition in teachers. Further studies are recommended to assess long-term sustainability and to consider follow-up strategies after program completion